Amphoteric Aqueous Hafnium Cluster Chemistry. Issue 21 (20th April 2016) - Goberna‐Ferrón, Sara; Park, Deok‐Hie; Amador, Jenn M.; Keszler, Douglas A.; Nyman, May
Abstract: Selective dissolution of hafnium‐peroxo‐sulfate films in aqueous tetramethylammonium hydroxide enables extreme UV lithographic patterning of sub‐10 nm HfO2 structures. Hafnium speciation under these basic conditions (pH>10), however, is unknown, as studies of hafnium aqueous chemistry have been limited to acid. Here, we report synthesis, crystal growth, and structural characterization of the first polynuclear hydroxo hafnium cluster isolated from base, [TMA]6 [Hf6 (μ‐O2 )6 (μ‐OH)6 (OH)12 ]⋅38 H2 O. The solution behavior of the cluster, including supramolecular assembly via hydrogen bonding is detailed via small‐angle X‐ray scattering (SAXS) and electrospray ionization mass spectrometry (ESI‐MS). The study opens a new chapter in the aqueous chemistry of hafnium, exemplifying the concept of amphoteric clusters and informing a critical process in single‐digit‐nm lithography. Abstract : Crossing the amphoteric desert : Beyond the acidic region, the chemistry of hafnium oxo‐hydroxo clusters has been a barren landscape. The first hafnium polynuclear hydroxo cluster was now isolated from basic solution, and it has surprising similarities to clusters isolated on the opposite end of the pH scale.